"We have to ask and only then do": Unpacking agency and autonomy in women's reproductive health in urban India. Issue 10 (2nd October 2016) - Raman, Shanti; Srinivasan, Krishnamachari; Kurpad, Anura; Ritchie, Jan; Razee, Husna
ABSTRACT: The limited autonomy and agency of women in developing countries is recognized as a key barrier to improving their reproductive health. Using an existing perinatal cohort in urban South India, we interviewed 36 women who had recently been through childbirth, and we carried out observations of family life and clinic encounters. Critical domains involved in women's agency and autonomy were women's participation in employment and group action and their mobility. Household decision making was considered a joint rather than individual responsibility. We call for a more nuanced understanding of these domains and their relationship to women's reproductive health, particularly for urban populations.